Projekt Dostopnost do kulturne dediščine ranljivim skupinam in pogledi nanj z vidika zaposlenih v sodelujočih muzejih - Palaić, Tina (Etnolog. Nova vrsta (Ljubljana), 2015)
The article presents modern museology concepts in the 21st century, including participation, inclusion, and accessibility, and investigates the changed ways of working and responsibility of museum workers. The views of the museum workers are then used to evaluate the project that implemented the above mentioned theoretical premises, i.e. Accessibility of cultural heritage to vulnerable groups. The project was carried out by the Slovene Ethnographic Museum in collaboration with other national museums and the National Gallery in 2013-2015. The authors conclude that the requirements of the public (in particular the members of vulnerable groups) require changes to museum work and emphasize the need for new employment.
Keywords: Slovenski etnografski muzej; projekti; cultural heritage; kulturna dediščina; inkluzija; osebe s posebnimi potrebami; dostopnost